Implementasi Pendidikan Karakter pada Mata Pelajaran Bahasa Arab di Madrasah Ibtidaiyah - Triani, Triani; Putra, Sudarmadi; Riyadi, Slamet (Nusantara: Jurnal Pendidikan Indonesia, 2023)
This study aims to investigate the implementation of character education in Arabic language learning at MIM Al-Qomariyah Klego. Character education focuses on strengthening moral and ethical values relevant to daily life. In the context of religious education, character development is an integral part of learning, including Arabic language instruction, which teaches Islamic values. This qualitative case study employs observation, interviews, and documentation to explore character education implementation. The results show that character education integration, active-participatory learning methods, and supportive media characterize Arabic language learning at MIM Al-Qomariyah Klego. Supporting factors include teacher commitment and conducive classroom management, while challenges include limited resources and time constraints. This study informs strategies to enhance character education quality in madrasahs.